Judicial power development issues in Russian conservative legal ideology during the second half of the XIX-th century - Konareva, Irina A.; Baboshina, Elena V.; Matyusheva, Tatiana N.; Rasskazov, Vyacheslav L.; Treskov, Aleksej P. (Linguistics and Culture Review, 2021)
The political and legal ideology of Russian conservatism becomes more and more popular in modern conditions. This scientific work is devoted to the study of the political and legal positions of Russian conservatives in the second half of the 19th century, who made a significant impact on the development of legal science. The problem of judiciary development is taken as a basis. The purpose of the study is to analyze the positions of Russian scholars and public and political figures who proposed a special concept of views regarding the place and role of the judiciary in the state mechanism of the Russian Empire during the second half of the 19th century. The hypothesis of the study is the presentation of a special approach to the consideration of conservative ideology in relation to the creation and organizational activity of the judicial system through the prism of national problems that developed in the Russian Empire during the second half of the 19th century. The methodological basis of the study is made up of general scientific, private, as well as special methods of cognition.